Factors Influencing Coconut Growers’ Decision-Making Process in Fertilizer Application through the Lens of Theory of Planned Behavior and Self-Determination Theory - Herath, C. S.; Wijekoon, Rusitha (International Coconut Community Journal, 2024)
The small-scale, poor, rural coconut growers in Sri Lanka are generally characterized by low productivity. The low yield of coconuts is primarily attributed to the improper application of fertilizers. The decision to apply fertilizer is mainly depends on the growers’ change in behaviour, in turn, influenced by the growers’ salient beliefs. Assessing the beliefs plays a significant role in understanding why farmers behave differently in making decisions regarding fertilizer application. The Theory of Planned Behaviour (TPB) and Theory of Self Determination (TSD) were employed to find a more realistic solution to the above research problem. Hence, the current research was carried out to observe the relationship between the beliefs of the coconut growers and their behaviour with respect to fertilizer application in coconut fields. Results of the study reveal that perceived behavioural control was the highest contributor to developing the intention followed by the attitude. Further, there is no influence from the social pressure for the intention development. Moreover, intrinsic motivation predicts the fertilizer application behaviour from intention in stronger strength than that of extrinsic motivation. Therefore, it can be concluded that motivation influences the intention-behavioural relationship. Consequently, it gives evidence for policymakers to introduce policy guidelines in order to enhance the use of fertilizer efficiently and effectively. And, motivation does have a moderating effect on coconut growers’ fertilizer application behaviour.